PENGARUH DISPLAY ROKOK TERHADAP UNPLANNED PURCHASE DAN BRAND SWITCHING PADA WARUNG TRADISIONAL - Said Muhammad Haidir; Muhammad Riza Firdaus; Ahmad Rifani (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
The purpose of this research were to analyze and to find out the effect of cigarette displays to unplanned purchases and brand switching at traditional outlets.This research used Non Probability Sampling and Purposive Sampling technique, with samples of 132 respondents of adult smokers. Totally there were 20 traditional outlets for the location of the research. The instrument of this research was questionnaires and the data were analyzed with Structural Equation ModelAMOS.The first result of this research showed that the cigarette displays had significant effects and positive trends to unplanned purchases. It means that because the cigarette displays were easy to be seen, easy to be obtained, easy to be remembered, and they were well arranged, they will encourage unplanned purchases. Another result showed that the cigarette displays did not have effects and negative trends to brand switching, it means that although cigarette displays were easy to be seen, easy to be obtained, easy to be remembered, and the cigarettes were well arranged, they did not affect consumers to do brand switching. Thus, brand switching was influenced by other factors.